Estudo da formação de biofilme depseudomonasaeruginosaatcc 9027 na superfície de carvão ativado impregnado com zinco ecobre em meio filtrante de leito fixo - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
Activated carbon is used in water filters due to its high adsorption capacity. However, microorganisms and organic matter can settle in its porous surface. The microorganisms consume organic matter and reproduce secrete polysaccharides, biofilm forming microbial these filters, which during the filtration process can be detached and contaminate the filtered water. In this work, samples of activated ch arcoal palm Elaeis guineensis coconut shell were impregnated with zinc, copper and combinations of these metals in the following weight contents: 0.100% Zn; 0.132% Cu; 0.066% Zn / Cu 0.055%; 0.041% Zn / Cu 0.101%; 0.062% Zn / Cu 0.092%, to assess the inhib itory effect on the formation of this method microbial growth Biofilm formati on on the surfaces of activated carbon was tested in flow using water with 6.398 c fu mL 1 Pseudomonas aeruginosa ATCC 9027. The coal samples were incubated in a humid chamber at room temperature for 24h. Sonication was performed for the detachment of cells associated with biofilms for counting the viable cells. There was the biofilm formation on the activated carbon ( with counting 6. 087 l og 10 cfu / 5g CA n i For samples activated carbon impregnated with metals ( there was a significant reduction in the formation of biofilms between CA ni and CAi except for the comparison CA ni and CAi 0.100% Zn (for p values < 0.05). Among the treatments CAi (activated carbon impregnated) significant inhibition was observed between samples containing zinc and copper alone compared to the combined samples, except for the comparison CAi 0.100% Zn and 0.066% Zn CAi / 0.055% Cu. The re was also a synergistic effect of the samples impregnated with zinc and copper simultaneously enhancing the inhibitory activity of biofilm formation when compared to the same action of isol ated metals and especially to non impregnated activated carbon (C A ni)
Keywords: Carvão biofilme; Pseudomonas aeruginosa; Zinco; Cobre; Activated carbon; Biofilm; Pseudomonas aeruginosa; Zinc; Cooper; CIENCIAS EXATAS E DA TERRA::QUIMICA